Bryophytes in Cibodas Botanical Garden: Diversity and Potential Uses - Ainun Nadhifah; Madinatul Khujjah; Pantalea Edelweiss Vitara; Ikhsan Noviady (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Research on the diversity of bryophytes in Indonesia has been generally accomplished. However, the publication of potential uses of this tiny plant is very limited. Cibodas Botanical Garden (CBG) as a center for ex-situ plant conservation has potential climate conditions as a location of moss growth. The study aims to collect bryophytes in CBG and to identify their potential uses. Purposive sampling method was used on various substrate (soil, rocks, trees). Some environmental parameters were also recorded, for instance, substrate type, temperature, and humidity. All of bryophytes collections were taken to the laboratory for the identification and saved in herbarium (CHTJ). A literature study was conducted to determine the potential uses of identified moss species. From 153 collection numbers recorded in CBG, there were 42 species which have potential use. In addition, there were 42 species that have the potential to be used as a medicinal plant, ornamental plants, uses in agriculture and environmental services. This study provides the initial information about the potential uses of mosses, liverworts, and hornworts particularly in Indonesia. Furthermore, these prospective utilization encourage the innovative research in Indonesia, particularly on alternative natural resources.